1996
DOI: 10.1152/jappl.1996.80.4.1214
|View full text |Cite
|
Sign up to set email alerts
|

Augmented hypoxic cerebral vasodilation in men during 5 days at 3,810 m altitude

Abstract: The fractional increase in cerebral blood flow (CBF) velocity (VCBF) from the control value with 5-min steps of isocapnic hypoxia and hyperoxic hypercapnia was measured by transcranial Doppler in six sea-level native men before and during a 5-day sojourn at 3,810 m altitude to determine whether cerebral vasoreactivity to low arterial O2 saturation (SaO2) gradually increased [as does the hypoxic ventilatory response (HVR)] or diminished (adapted, in concert with known slow fall of CBF) at altitude. A control re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 0 publications
7
48
1
1
Order By: Relevance
“…This phenomenon has previously been suggested linked to the increased hypercapnic CVR after 2 to 4 and 16 days at high altitude. 8,10,15 In addition, the association between hypercapnic CVR and resting capillary HCO 3 − at SL, HA0, HA3, and HA22 ( Figure 5) observed in the present study, supports this notion.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This phenomenon has previously been suggested linked to the increased hypercapnic CVR after 2 to 4 and 16 days at high altitude. 8,10,15 In addition, the association between hypercapnic CVR and resting capillary HCO 3 − at SL, HA0, HA3, and HA22 ( Figure 5) observed in the present study, supports this notion.…”
Section: Discussionsupporting
confidence: 88%
“…3 This will be discussed in greater detail elsewhere. The consequence of high-altitude exposure on cerebrovascular function is controversial, as CVR has been reported to be increased, 8,10,14,15 unchanged, 11,13,16 or even reduced. 7,9,12 In the present study, we observed a decreased hypercapnic CVR at HA0 followed by an increased hypercapnic CVR at HA3 and HA22 compared with SL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular questions to which we sought answers included whether the secondary fall in CBF could be prevented by the maintenance of isocapnia and whether there was any evidence of acclimatization to the hypocapnia of the poikilocapnic protocol. There has also been a report that the sensitivity of CBF to acute changes in the level of hypoxia/hypercapnia is altered following a period of acclimatization to hypoxia (Jensen et al 1996). An additional purpose of this investigation was to examine whether we could replicate this observation, and if so, whether the results from the poikilocapnic and isocapnic protocols differed with respect to this phenomenon.…”
mentioning
confidence: 99%
“…It has been reported that the oxygenation delivery of brain tissue is associated with the cerebral blood flow velocities [11][12][13]. The decrease of CBFV in MCA means that the oxygenation delivery of brain tissue could come down after 1h driving.…”
Section: Advanced Engineering Forum Vols 2-3mentioning
confidence: 99%